2017
DOI: 10.1515/rjim-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of short-term effect of L-Citrulline on endothelial function via FMD to NMD ratio in known CAD patients: A randomized, cross-over clinical trial (Clinical trial number: NCT02638727)

Abstract: Background. Recent studies have confirmed the essential and paramount role of the L-Citrulline on the nitric oxide regulation and the endothelial function improvement.Materials and Methods. In this cross-over clinical trial, thirty patients, diagnosed with coronary artery disease (CAD) and flow mediated dilation to nitroglycerin dependent vasodilation (FMD/NMD) ratio less than 1, were included. The patients were randomly divided into two groups of 15 patients and underwent treatment by L-Citrulline or placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Based on the results of this study, it can be concluded that five days of supplementation with L-citrulline does not impact that rate at which lactate is cleared from the blood during active recovery. While prior research indicates that supplementation with L-citrulline augments vasodilatory responses in the body (Gonzales et al 2017;Safi et al 2017) and other research suggests that augmenting vasodilation facilitates greater lactate removal from the blood (Gladden 2000;2004), the results of the current investigation do not support this relationship. Research up to this point on the effects of L-citrulline supplementation and exercise-induced blood lactate are mixed.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Based on the results of this study, it can be concluded that five days of supplementation with L-citrulline does not impact that rate at which lactate is cleared from the blood during active recovery. While prior research indicates that supplementation with L-citrulline augments vasodilatory responses in the body (Gonzales et al 2017;Safi et al 2017) and other research suggests that augmenting vasodilation facilitates greater lactate removal from the blood (Gladden 2000;2004), the results of the current investigation do not support this relationship. Research up to this point on the effects of L-citrulline supplementation and exercise-induced blood lactate are mixed.…”
Section: Discussioncontrasting
confidence: 88%
“…Our study design and hypothesis were based upon the previously mentioned findings that both acute (Raghavan and Dikshit 2001;Sureda et al 2009;Mori et al 2015;Le Roux-Mallouf et al 2017) and prolonged supplementation (i.e. 7þ days) (Schwedhelm et al 2008;Alsop and Hauton 2016;Gonzales et al 2017;Safi et al 2017) with L-citrulline have been previously reported to enhance vasodilation by facilitating production of nitric oxide. Thus, while the measurement of NO x would have provided information as to the magnitude of the effect provided by L-citrulline, we are very confident that NO x levels were sufficiently elevated and we do not believe that the lack of this measurement undermines the validity of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…1, seventeen studies involved L-citrulline supplementation. Six studies with eight relevant study arms investigated postprandial effects (24)(25)(26)(27)(28)(29) , while twelve studies with twelve relevant study arms investigated longer-term effects (27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) . One trial investigated both postprandial and longer-term effects (27) .…”
Section: Study Selectionmentioning
confidence: 99%
“…Three studies did not receive any funding (30,36,40) , while one study did not report any information on funding or grants (27) . Ten studies mentioned that their supplements were provided by Pronat Laboratories, NOW Foods, Milne Fruits or Cobell Ltd, without receiving any direct funding (31,32,35,37,39,(45)(46)(47)(48)(49) , while two studies reported that they received funding from the National Watermelon Promotion Board (41,44) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation